2020
DOI: 10.1029/2019ja027296
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Reconnection Within a Flux Rope‐Type Dipolarization Front

Abstract: On 8 September 2018, at nearly 14:51:30 UT, the Magnetospheric Multiscale (MMS) spacecraftencountered an electron diffusion region near the center of a flux-rope type dipolarization front. The observed signature of the magnetic field in geocentric solar ecliptic included a bipolar B z coinciding with a peak in B y and |B| as is typical for a flux rope. At the same time, all three spacecraft with available plasma data observed a decrease in density and an increase in temperature over ion scales near the reversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 55 publications
(105 reference statements)
3
13
1
Order By: Relevance
“…We note that the strong variations of the B z field seen in Figure 9a made applying the LMN coordinate system to Event 3 difficult. This is because the L component in LMN would be close to the x direction in GSM, as seen in earlier studies (Marshall et al., 2020 ). This might suggest the filamentation of the original tail current sheet and even its strong bending, which would distort the global picture for this WS predicted by DM reconstruction (Figure 8 ).…”
Section: Observationssupporting
confidence: 69%
“…We note that the strong variations of the B z field seen in Figure 9a made applying the LMN coordinate system to Event 3 difficult. This is because the L component in LMN would be close to the x direction in GSM, as seen in earlier studies (Marshall et al., 2020 ). This might suggest the filamentation of the original tail current sheet and even its strong bending, which would distort the global picture for this WS predicted by DM reconstruction (Figure 8 ).…”
Section: Observationssupporting
confidence: 69%
“…Journal of Geophysical Research: Space Physics electron diffusion region near the center of it (Marshall et al, 2020). J Á E increases to 0.89 nW/m 3 as J y and E y climb to their local maximum and remains positive until after B z drop from its maximum (Figure 2m).…”
Section: 1029/2020ja028568mentioning
confidence: 97%
“…Simultaneously, the intensification of current in the Y and −Z directions can be clearly seen during the DF interval (Figure 2k). This case has been studied in detail and indeed defined as a FR‐type DF with an electron diffusion region near the center of it (Marshall et al, 2020). J ⋅ E increases to 0.89 nW/m 3 as J y and E y climb to their local maximum and remains positive until after B z drop from its maximum (Figure 2m).…”
Section: Case Studymentioning
confidence: 99%
“…The LMN unit vectors, specified in the Geocentric Solar Ecliptic (GSE) coordinate system, have the following components: e L = [−0.11648, +0.27887, +0.95324], e M = [+0.07826, +0.95936, −0.27110], and e N = [−0.99010, +0.04302, −0.13357]. This LMN coordinate system is nearly the same as the one that was determined by Marshall et al (2020), differing from the latter mainly by the opposite signs of the M and N orts. The normal component of the structure velocity was determined by the timing method (Russell et al, 1983), and two other components were estimated as the average ion velocity within the 1.5 s reconstruction interval 14.51.30.25-14.51.31.75 UT.…”
Section: Steady Statementioning
confidence: 92%
“…The reconstruction of Korovinskiy et al (2021) has also revealed the signatures of CS time dependence, observed during the first 0.4 s, when the out-of-plane component E y demonstrated some reduction and the function V ey (A) was not single-valued (see Figures 2A, 3E of the cited paper), which resulted in a low reconstruction accuracy within this interval (see Figure 6 of Korovinskiy et al (2021) or Figure 3). To investigate the model failure in an unsteady CS, we addressed the event of September 8, 2018, when at nearly 14:51:30 UT, MMS encountered an EDR near the center of a flux-rope type dipolarization front (Marshall et al, 2020). The reconstruction is performed in the co-moving LMN reference frame.…”
Section: Steady Statementioning
confidence: 99%